Cyclotella iranica sp. nov. (Bacillariophyta: Coscinodiscophyceae), a new diatom from the Karaj River, Iran - Kheiri, Somayyeh; Nejadsattari, Taher; Asri, Younes; Hamdi, Seyed Mohammad Mehdi; Spaulding, Sarah; Edlund, Mark B. (Phytotaxa, 2013)
Cyclotella iranica sp. nov. is described from the Karaj River, Iran. The morphology of Cyclotella iranica is documented with light and scanning electron micrographs and discussed in comparison with several related species: Cyclotella fottii, C. delicatula, C. andancensis var. adnanensis, C. andancensis var. bauzilensis and C. andancensis var. bipolaira. Cyclotella iranica shares with these related Cyclotella species the following features: unequal stria pattern, one sessile rimoportula and several marginal fultoportulae. It is distinguished from them by the position of central fultoportula(e), which is (are) situated at the central end of the striae. It is known only from the type locality; the autecology of Cyclotella iranica shows that it is tolerant of nutrient and organic enrichment.